Refleksi Pemimpin Yang Memberdayakan Berdasarkan Keluaran 18:18-24 - Hergyana Saras Ningtyas; Sriyati Sriyati (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2021)
The focus of leadership is not about position. An important role in leadership is to help those being led to grow in Jesus Christ. This study discusses the Reflections of Empowering Leaders Based on Exodus 18: 18-24. The objective is to identify the role of leaders in the empowering principles studied from Exodus 18: 18-24 regarding the leadership of Moses. One of the reasons for Moses' leadership to be ineffective was that Moses was leading alone. Therefore Jethro, who was Musa's father-in-law as well as a priest in Midian known as a prophet, suggested that Moses develop the principle of empowering capable people to become leaders for the smaller groups under his leadership. The methodology used is literature research using primary sources from books, journals and previous research as a source of study. The primary data is then analyzed and synthesized to become the novelty discussed in this study. So the orientation in empowering leadership is an effort to help the individual being led reach a better stage so that it is more light than Musa's single leadership. The leadership principles discussed include delegating leadership, increasing responsibility, increasing capacity, training independence and being willing to learn and be taught. Thus, this leadership can have a wider influence and create empowered individuals, independent of certain situations or organizations. Today's leadership succession requires to form leaders who excel in the face of competition, innovation, and leadership succession skills that can be manifested in empowering leadership. An empowering leader is a solution to leadership problems in the Indonesian nation, the church and the family as the smallest unit in the organization.